PENGEMBANGAN MEDIA KOMIK CERITA ANAK UNTUK MENINGKATKAN KETERAMPILAN LITERASI BACA TULIS PADA SISWA KELAS 4 SEKOLAH DASAR - Deny Chandra Anugerah, Fransisko; Bagus Amirul Mukmin; Alfi laila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This development research is based on the results of observations and interviews that learning Indonesian reading and viewing still has several students whose interest in reading is still low. Based on the results of observations and interviews that became the basis of the research entitled the development of children's story comic media to improve reading and writing literacy skills in grade 4 elementary school students. The media developed were tested for validity, effectiveness, and practicality. This research is a type of development research or Research and Development using the ADDIE model. In this study were students and teachers of grade 4 SDN Ngoro 2. Data collection techniques in the research conducted using observation, interviews, questionnaires, and tests with quantitative and qualitative data analysis. The purpose of the study was to determine the quality of the learning media products developed based on aspects of validity, effectiveness, and practicality. The results of the comic development research are as follows: (1) comic media is declared valid with results of 87% from material validation and 78.75% from media validation, (2) comic media is declared very practical with results of 96% from teacher responses and 98.26% from student responses, (3) comic media is declared very effective after the evaluation test or posttest with the results of the completion of the limited trial showing an average of 88.6 and the extensive trial showing an average value of 87.6.   Keywords : comics, learning media, indonesian